Liver protective effect of ursodeoxycholic acid includes regulation of ADAM17 activity - Buryova, Halka; Chalupsky, Karel; Zbodakova, Olga; Kanchev, Ivan; Jirouskova, Marketa; Gregor, Martin; Sedlacek, Radislav (BMC gastroenterology, 2013)
BACKGROUND: Ursodeoxycholic acid (UDCA) is used to treat primary biliary cirrhosis, intrahepatic cholestasis, and other cholestatic conditions. Although much has been learned about the molecular basis of the disease pathophysiology, our understanding of the effects of UDCA remains unclear. Possibly underlying its cytoprotective, anti-apoptotic, anti-oxidative effects, UDCA was reported to regulate the expression of TNFα and other inflammatory cytokines. However, it is not known if this effect involves also modulation of ADAM family of metalloproteinases, which are responsible for release of ectodomains of inflammatory cytokines from the cell surface. We hypothesized that UDCA modulates ADAM17 activity, resulting in amelioration of cholestasis in a murine model of bile duct ligation (BDL). METHODS: The effect of UDCA on ADAM17 activity was studied using the human liver hepatocellular carcinoma cell line HepG2. Untransfected cells or cells ectopically expressing human ADAM17 were cultured with or without UDCA and further activated using phorbol-12-myristate-13-acetate (PMA). The expression and release of ADAM17 substrates, TNFα, TGFα, and c-Met receptor (or its soluble form, sMet) were evaluated using ELISA and quantitative real-time (qRT) PCR. Immunoblotting analyses were conducted to evaluate expression and activation of ADAM17 as well as the level of ERK1/2 phosphorylation after UDCA treatment. The regulation of tissue inhibitor of metalloproteinases-1 (TIMP-1) by UDCA was studied using zymography and qRT-PCR. A mouse model of acute cholestasis was induced by common BDL technique, during which mice received daily orogastric gavage with either UDCA or vehicle only. Liver injury was quantified using alkaline phosphatase (ALP), relative liver weight, and confirmed by histological analysis. ADAM17 substrates in sera were assessed using a bead multiplex assay. RESULTS: UDCA decreases amount of shed TNFα, TGFα, and sMet in cell culture media and the phosphorylation of ERK1/2. These effects are mediated by the reduction of ADAM17 activity in PMA stimulated cells although the expression ADAM17 is not affected. UDCA reduced the level of the mature form of ADAM17. Moreover, UDCA regulates the expression of TIMP-1 and gelatinases activity in PMA stimulated cells. A BDL-induced acute cholangitis model was characterized by increased relative liver weight, serum levels of ALP, sMet, and loss of intracellular glycogen. UDCA administration significantly decreased ALP and sMet levels, and reduced relative liver weight. Furthermore, hepatocytes of UDCA-treated animals retained their metabolic activity as evidenced by the amount of glycogen storage. CONCLUSIONS: The beneficial effect of UDCA appears to be mediated in part by the inhibition of ADAM17 activation and, thus, the release of TNFα, a strong pro-inflammatory factor. The release of other ADAM17 substrates, TGFα and sMet, are also regulated this way, pointing to a general impact on the release of ADAM17 substrates, which are pivotal for liver regeneration and function. In parallel, UDCA upregulates TIMP-1 that in turn inhibits matrix metalloproteinases, which destroy the hepatic ECM in diseased liver. This control of extracellular matrix turnover represents an additional beneficial path of UDCA treatment.
Keywords: Ligation; játra; Bile Ducts; Humans; ADAM Proteins; Proto-Oncogene Proteins c-met; proteiny ADAM; ligace; transformující růstový faktor alfa; lidé; zvířata; myši; Ursodeoxycholic Acid; cholagoga a choleretika; Hep G2 Cells; Cholestasis; Mice; žlučové cesty; TNF-alfa; Liver; buňky Hep G2; kyselina ursodeoxycholová; protein ADAM17; protoonkogenní proteiny c-met; MAP Kinase Signaling System; Tumor Necrosis Factor-alpha; Hepatocytes; Animals; ADAM17 Protein; hepatocyty; Transforming Growth Factor alpha; MAP kinasový signální systém; cholestáza; Cholagogues and Choleretics